Case report Severe inverted acne associated with pyoderma gangrenosum and complicated by sepsis - Bergler-Czop, Beata; Brzezińska-Wcisło, Ligia; Trzmiel, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Inverted acne and pyoderma gangrenosum are both rare inflammatory skin conditions that are associated with systemic inflammatory diseases. Acne inversa is a chronic or relapsing scarring disease, manifested by recurrent formation of abscesses, fistulating sinus and scarring of the axillae, groins and perineum occurring predominantly in women, with onset at puberty. The association with Crohn disease, psoriasis and pyoderma gangrenosum, as well as the seronegative arthropathies, suggests common immunopathogenesis. All patients required multiple therapeutic agents because their diseases ( acne inversa and pyoderma gangrenosum ) were often poorly responsive to standard therapies. We describe the case of a 53-year-old man because of severe acne inversa with pyoderma gangrenosum complicated by sepsis.